Collembola Poduromorpha from two littoral areas of northern Rio de Janeiro, Brazil - Da Silveira, Tatiana Cristina; de Mendonça, Maria Cleide (Zootaxa, 2020)
Knowledge on Poduromorpha fauna from the littoral of Rio de Janeiro mainly come from studies conducted in “restinga” areas of Itaipuaçu, Maricá, and Marambaia. In this study two “restinga” areas were sampled for the first time to increase the taxonomic knowledge of Poduromorpha in littoral areas of Rio de Janeiro: Costa do Sol State Park and Restinga de Jurubatiba National Park, located respectively at Lake Region (“região dos lagos”) and at northern Rio de Janeiro State. The analysis of the material showed the presence of six families, 14 genera and 20 species. All records are new for both areas; Neanuridae had the highest diversity, with seven genera and 10 species. One of them, Paleonura Cassagnau, 1982, was registered for the first time in the littoral of Rio de Janeiro. A key was proposed for the Poduromorpha genera found in the littoral of Rio de Janeiro.